Study on relationship between burr and cutting clearance of commonly used sheet metals in automotive industry in Malaysia in relation to piercing and blanking processes - Omar Baki, Mohamad Faezal (2003)
This thesis paper presents a study on the relationship between burr and cutting clearance of commonly used sheet metal in automotive industry in Malaysia in relation to piercing and blanking processes. It reviews the result between mechanical and hydraulic presses and between SPCC (Cold rolled material) and SPHC (Hot rolled material) which are commonly used in automotive industry. The chosen of these two materials are because of its high usage in automotive industries in Malaysia. SPCC is most popular because of its attractive surface finished. It is suitable for bending and simple drawing operations. For SPHC, suitable mainly for flat sheets or simple bending operations and simple drawing operations are also possible.